A practical treatise on segmental and elliptical oblique or skew arches setting forth the principles and details of construction in clear and simple terms - Bell, George Joseph (Chas. Thurnam and Sons, 1896)
Here, George Joseph Bell makes available the results of his calculations for 72 oblique bridges, designed to suit almost any situation, in spans from 10 feet to 50 feet advancing by 5 feet, and from 35 degrees to 70 degrees, advancing by 5 degrees.